2016
DOI: 10.5897/jahr2015.0353
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the practice of exclusive breastfeeding among HIV-positive mothers in sub-Saharan Africa: A Scoping Review of counselling, socioeconomic and cultural factors

Abstract: The World Health Organization (WHO) recommends exclusive breast-feeding (EBF) for HIV exposed infants for six months; this is considered best practice for reducing mother-to-child transmission of HIV in the postpartum period. This is a scoping review of the barriers affecting women's decision-making and choice to sustain the practice of EBF in sub-Saharan Africa (SSA). An online literature search via PubMed, Science Direct, Google Scholar, WHO and Joint United Nations Programme on HIV and AIDS (UNAIDS) website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…In the literature, the EBF among HIV infected mothers is affected by inadequate counselling on EBF practice [ 21 , 22 ], cultural and family influence [ 21 , 23 ], socio-economic factors [ 23 ],fear of stigmatization [ 22 , 23 ], maternal lack of decision power [ 21 ] and fear of vertical transmission of HIV to infant [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the EBF among HIV infected mothers is affected by inadequate counselling on EBF practice [ 21 , 22 ], cultural and family influence [ 21 , 23 ], socio-economic factors [ 23 ],fear of stigmatization [ 22 , 23 ], maternal lack of decision power [ 21 ] and fear of vertical transmission of HIV to infant [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…58 A few studies investigated ART exposure and its effect on the health of mothers and the growth of their infants (n = 4; 9.5%). 8,9,61,78 ART exposure appeared to increase infant mortality and negatively affect neurodevelopment in breastfed HE infants, 6 and some studies reported growth deficits in HI and HE infants receiving ART, when compared with the growth of HU infants. Further research investigating the long-term influence of ART on the neurodevelopment of breastfeeding HI and HE infants would be valuable.…”
Section: Hi and He Infant Growth And Developmentmentioning
confidence: 99%
“…64,73,81,83 Additional social factors we found that should be considered by health care professionals were the fear of EBF practice and the feeding practices and beliefs of significant others, for example, replacement mothers' and partners' adherence to EBF. 8 Facilitators to maternal knowledge, attitudes, and practices regarding breastfeeding did not feature predominantly in the reviewed literature. The few facilitators found were social and familial support, economic independence, and material resources.…”
Section: Barriers and Facilitators To Feeding Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Despite these negative consequences, early BF cessation remains prevalent among mothers living with HIV infection in part because of the fear of mother-to-child transmission. 6 8 …”
Section: Introductionmentioning
confidence: 99%